Oberhausser, Ann M.; Fluri, Jennifer L.; Whitson, Risa i Mollet, Sharlene (2018). Feminist Spaces: Gender and Geography in a Global Context - Ortiz Guitart, Anna (Documents d’Anàlisi Geogràfica, 2020)
Oberhausser, Ann M.; Fluri, Jennifer L.; Whitson, Risa i Mollet, Sharlene (2018) Feminist Spaces: Gender and Geography in a Global Context Oxon: Routledge, 229 p. ISBN 978-1138924536